Propuesta de un modelo de gestión del talento humano por procesos en una Unidad Educativa. - Tenorio Panchi, Brithney Nicole (2023)
The current work had as aim to propose a Human Talent Management Model by processes to improve work performance in the "La Fontaine" High School Educational Unit. The main problem to be solved, was the staff low performance in the educational institution, manifested in a limited professional performance and the leadership lack, what demotivated the administrative and teaching staff. For addressing this problem, it was used a work methodology, what combined quantitative and qualitative approaches. It was collected information, through numerical and statistical interpretations, using research instruments, and was made a bibliographical-documentary research to theoretically support the study. The results revealed, which the rewards and recognition system showed a tendency towards neutrality, with a significant percentage 33.33% respondents without a clear opinion. While one group was highly satisfied, another considered the system highly unsatisfactory and unsatisfactory, indicating discontent and unfulfilled expectations. The project practical application consisted in the Human Talent Management Model creation, what included four key dimensions: recruitment and selection, training, performance assessment, and remuneration, compensation and benefits. They were developed optimization strategies based on the model indicators to enhance all these dimensions.